Territorial distribution of projects contracted at the level of Cohesion Policy 2014-2020 - Marin Florian (Ekonomika Poljoprivrede (1979), 2020)
The article aims to identify the territorial distribution of the projects contracted within the operational programs that form an integral part of the Cohesion Policy 2014 - 2020. The analysis is performed in the context in which the territoriality of the investments financed by the Cohesion Policy represents an important variable for ensuring its success. In this article, we proceeded to identify the investment profile used by each county, profile exposed based on a methodology of calculation based on the themes financed by each operational program respectively of the projects contracted at the level of each operational program. Two variables were used in the analysis, namely the number and value of the projects contracted until 30.09.2019. The article highlights the existence of a significant territorial concentration of the projects contracted at the level of a small number of counties. Also, the infrastructure and regional development are the needs considered to be the most present at the level of the projects contracted at the level of Cohesion Policy.